Antihypertensive treatment with hydrochlorothiazide-hydralazine combination aggravates medial vascular calcification in CKD rats with mineral bone disorder - Larivière, Richard; Ung, Roth-Visal; Picard, Sylvain; Richard, Darren E.; Mac-Way, Fabrice; Agharazii, Mohsen (Frontiers in Cardiovascular Medicine, 2023)
Background: Arterial stiffness and medial vascular calcification, leading to isolated systolic blood pressure (BP), are major cardiovascular risk factors in patients with chronic kidney disease (CKD) and mineral bone disorders (MBD). The impact of BP on MBDinduced medial vascular calcification in CKD remains uncertain. We investigated whether BP reduction improves arterial stiffness and medial vascular calcification in a rat model of CKD-MBD.Methods: CKD was induced in Wistar rats by subtotal nephrectomy. Then, MBD was generated by a Ca/P-rich diet with calcitriol supplementation to induce medial vascular calcification. Two antihypertensive treatments were evaluated: 1) the angiotensin AT1 receptor antagonist losartan, and 2) the combination of the thiazide diuretic hydrochlorothiazide and the direct vasodilator hydralazine (HCTZ/HY). After 5 weeks, mean BP (MBP), pulse pressure (PP), and pulse wave velocity (PWV) were determined.Vascular calcification was assessed in the thoracic aorta.Results: While MBP was similar in CKD-MBD and control CKD rats, PP and PWV were increased in CKD-MBD rats. The heightened arterial stiffness in CKD-MBD rats was associated with diffused medial calcification along the thoracic aorta. Although both losartan and HCTZ/HY reduced MBP in CKD-MBD rats, losartan did not affect PP and PWV nor medial vascular calcification, whereas HCTZ/HY, unexpectedly, further increased arterial stiffness and medial vascular calcification.In the rat model of CKD-MBD, antihypertensive treatment with losartan did not affect arterial stiffness or medial vascular calcification. However, HCTZ/HY treatment aggravated arterial stiffness and vascular calcification despite a similar reduction of MBP, 23 suggesting a blood pressure-independent mechanism for vascular calcification.